Determination of air side heat transfer coefficient in a mini-channel heat exchanger using Wilson Plot method - Thoo, K.K. (2013)
In this study, the air side heat transfer coefficient of an aluminium mini-channel heat exchanger was investigated for single-phase flow in the mini-channel, with water in the tubes and air on the outside. Research methods included hydraulic tests on a single mini-channel tube, Wilson Plot experiments and experiment validation. Results obtained from the hydraulic test showed that turbulent flow occurred in the tube at a Reynolds number of 830. Wilson Plot experiments were conducted to determine air side heat transfer coefficient of the heat exchanger. The tube side Reynolds number was maintained above 1000 to ensure turbulent flow and tube side heat transfer coefficient was calculated using Gnielinski equation for turbulent flow. The air side heat transfer coefficients obtained from the Wilson Plot experiments were in good agreement with known correlations. The outcome of this study is to use the air side heat transfer coefficient to calculate the performance of refrigerant condensers for different tube pass ratios and flow pass configurations. Â© Published under licence by IOP Publishing Ltd.